2002
DOI: 10.1152/jn.00593.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Mechanical Stimulation by Inflammatory Mediators and by Mild Burn in Canine Visceral Nociceptors In Vitro

Abstract: Hyperalgesia to mechanical stimulation and heat is commonly observed in inflamed conditions. Although sensitization to heat is well documented and its mechanism has also been well studied, it remains unclear whether and how nociceptors are sensitized to mechanical stimulation. Therefore we conducted in vitro investigation of which inflammatory mediators (bradykinin, histamine, prostaglandin E2, and protons) sensitize nociceptors to suprathreshold mechanical stimulation and at what concentrations. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
1
34
1
Order By: Relevance
“…Such preferential activation is reminiscent of the effect of MC degranulation on C-unit meningeal nociceptors (Levy et al, 2007). We found that histamine also preferentially promotes mechanical sensitization of C-units, findings that are in agreement with its effect on testicular nociceptors (Koda and Mizumura, 2002). Our study further showed that both the activation and sensitization mediated by histamine are short-lived, suggesting that histamine alone may not be able to sustain the prolonged activation of meningeal nociceptors evoked by MCs degranulation.…”
Section: Discussionsupporting
confidence: 85%
“…Such preferential activation is reminiscent of the effect of MC degranulation on C-unit meningeal nociceptors (Levy et al, 2007). We found that histamine also preferentially promotes mechanical sensitization of C-units, findings that are in agreement with its effect on testicular nociceptors (Koda and Mizumura, 2002). Our study further showed that both the activation and sensitization mediated by histamine are short-lived, suggesting that histamine alone may not be able to sustain the prolonged activation of meningeal nociceptors evoked by MCs degranulation.…”
Section: Discussionsupporting
confidence: 85%
“…However, in the same preparation, neither PGE 2 nor the "inflammatory soup" (composed of PGE 2 , bradykinin, histamine, and serotonin) caused a decrease in the mechanical von Frey threshold of the mechanosensitive C-fibers, and the responses to suprathreshold mechanical stimuli remained unaltered as well (403,639). In a study on polymodal nociceptors of the isolated dog testis, PGE 2 did not alter the von Frey threshold but increased the number of spike discharges evoked by mechanical stimulation and this effect was mimicked by forskolin (370). PGE 2 and/or PGI 2 caused a mechanical sensitization of articular afferents of the cat knee joint, rat ankle and knee joint (53, 54, 564,636,638).…”
Section: Prostanoid-induced Sensitization To Mechanical Stimulimentioning
confidence: 94%
“…BK also lowered the mechanical threshold of muscle nociceptors in vivo (Mense and Meyer 1988) and sensitized visceral nociceptors to mechanical stimulus in vitro (Koda and Mizumura 2002). In addition, prostaglandin E2, histamine (Koda and Mizumura 2002), and ATP (Page et al 2000) are known to sensitize nociceptor responses to mechanical stimulus. All these substances also sensitize nociceptors to heat (Koda et al 1996;Kress and Guenther 1999;Mizumura et al 1993;Petho et al 2001;Yajima et al 2005), although the concentration needed to sensitize sensory receptors to mechanical stimulus is higher than that needed to sensitize them to heat (Koda et al 2002).…”
Section: Effects Of Eccmentioning
confidence: 97%
“…Treatment with low pH was found to cause a significant and lasting decrease of the mechanical thresholds in almost all C-fibers in rat skin-nerve preparations in vitro (Steen et al 1992). BK also lowered the mechanical threshold of muscle nociceptors in vivo (Mense and Meyer 1988) and sensitized visceral nociceptors to mechanical stimulus in vitro (Koda and Mizumura 2002). In addition, prostaglandin E2, histamine (Koda and Mizumura 2002), and ATP (Page et al 2000) are known to sensitize nociceptor responses to mechanical stimulus.…”
Section: Effects Of Eccmentioning
confidence: 97%
See 1 more Smart Citation